2002
DOI: 10.1002/ana.10243
|View full text |Cite
|
Sign up to set email alerts
|

Sudomotor testing predicts the presence of neutralizing botulinum A toxin antibodies

Abstract: The increasing number of patients being treated with botulinum toxin A complex (BoNT/A) has led to a higher incidence of neutralizing anti-BoNT/A antibodies (ABAs). Because BoNT/A is known to inhibit sweating, here we report sudometry as a possibility for predicting the presence of ABA. Sixteen patients suffering from spasmodic torticollis were selected: in 2 patients, BoNT/A treatment continued to be effective, in 9 patients, the treatment effect was impaired, and in 5 patients, secondary treatment failure de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…An alternative explanation for our results might be that BoNT/A interferes with active sudomotor-driven vasodilation in human hairy skin [23]. Sudomotor fibers can be blocked by BoNT/A [4]. Since electrical current used in our experiments also activates peripheral sudomotor fibers and thereby induces local acetylcholine release and axon reflex sweating [45], which is similar in size and spatial extent to the neurogenic flare [33], reduction of flare could readily be explained by blocking these "vasodilatory" sudomotor fibers.…”
Section: S Bont/a Reduces Neurogenic Flarementioning
confidence: 77%
“…An alternative explanation for our results might be that BoNT/A interferes with active sudomotor-driven vasodilation in human hairy skin [23]. Sudomotor fibers can be blocked by BoNT/A [4]. Since electrical current used in our experiments also activates peripheral sudomotor fibers and thereby induces local acetylcholine release and axon reflex sweating [45], which is similar in size and spatial extent to the neurogenic flare [33], reduction of flare could readily be explained by blocking these "vasodilatory" sudomotor fibers.…”
Section: S Bont/a Reduces Neurogenic Flarementioning
confidence: 77%
“…QSART This was performed in all subjects in a session before BoNT/B injection to provide baseline values. As there is no di¡erence between right and left legs in healthy subjects (Braune et al, 2001;Birklein et al, 2002), we pooled measurements for both legs (AUC of 534 arbitrary units; range 379^744). After 3 wk, QSART was reduced to 18% of baseline (range 0^64) and even absent in 10 of 15 subjects with BoNT/B doses of 62.5 MU or more (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…17,18 In a more complex procedure, additional injections with carbachol (quantitative sudomotor axon reflex test ϭ QSART), sweat chambers, and the iodine-starch reaction as described by Minor were used. 19 The author suggested that the QSART might be powerful enough to estimate the height of BoNT/A-AB titers.…”
Section: Discussionmentioning
confidence: 99%